Investigating pre-service EFL teachers’ language mindset and epistemological beliefs - Seda SIVACI; Sıvacı, Seda (My University, 2023)
Learning a new language is widely recognized as a persistent, intricate, and demanding endeavor for learners. Along this journey, various challenges are expected to arise, potentially hindering effective communication. Therefore, Language Learning Mindsets (LLMs) are considered crucial indicators in understanding why learners react differently to these adversities. Additionally, LLMs encompass how learners respond to the learning process, influencing their goals, learning strategies, and effort, consequently impacting their motivation for language acquisition. The goal of this study is to explore the potential relationship betwixt language mindsets (LLMs) and epistemological beliefs among pre-service English as a Foreign Language (EFL) teachers. To accomplish this, 141 pre-service English teachers participated in the study. Quantitative data were gathered using the Language Mindsets Inventory (LMI) and the Epistemological Beliefs Questionnaire. The quantitative data analysis involved the application of descriptive statistics and regression analyses. The findings demonstrated that the sub-dimensions of epistemological beliefs, namely, learning effort and certainity in knowledge, significantly predicted and positively influenced incremental views during the language learning process. Specifically, their respective impacts on the outcome variable concerning treatment differences were somewhat less pronounced but remained in the positive range. Moreover, while innate/fixed ability significantly influenced entity views of language learning, the sub-dimensions of learning process/expert knowledge and learning effort did not serve as significant predictors for entity views regarding language learning. These findings hold implications for the development of EFL teachers' beliefs, suggesting that their perception of innate learning ability, which is transferable, significantly affects their approach to language learning.
Keywords: Language mindset; epistemological belief; pre-service teachers; language learning